Assessment of Northern Jordanian adolescents' knowledge and attitudes towards asthma - Alkhawaldeh, A.; ALBashtawy, M.; Omari, O.; Wynaden, Dianne; Alhalaiqa, F.; Hamadneh, S.; Aljohani, K.; Al-Awamreh, K.; Khatatbeh, M. (RCN Publishing Co, 2017)
Background Asthma is a chronic illness of the airways that can cause a persistent cough. The illness affects a significant population of young people worldwide and can affect their ongoing quality of life. Aim To explore Jordanian adolescents' knowledge and attitudes to asthma. Method A cross-sectional research design was used with a convenience sample of 302 adolescents from six schools in northern Jordan, who completed a self-reported knowledge and attitude survey. Results Although the adolescents had an adequate knowledge level about asthma, several areas of knowledge deficit were identified and some negative attitudes were demonstrated. No significant association was found between adolescents' level of knowledge and their attitudes to adolescents with asthma. Conclusion Jordanian adolescents need more educational programmes about living with life-changing chronic illnesses such as asthma, and about how the knowledge and positive attitudes of peer groups can normalise the illness for the affected person, enhancing their quality of life.